Constitutional politics in Canada and the United States - Newman, Stephen L. (SUNY series in American constitutionalism., 2004)
The Canadian constitutional reforms of 1982, which included a Charter of Rights and Freedoms analogous to the American Bill of Rights, brought about a convergence with American constitutional law. As in the U.S., Canadian courts have shown themselves highly protective of individual rights, and they have not been shy about assuming a leading and sometimes controversial political role in striking down legislation. In clear and easy-to-understand language, the contributors not only chart, but also explore, the reasons for areas of similarity and difference in the constitutional politics of Canada and the United States. Book jacket.